Measuring Inequality of Opportunities in Latin America and the Caribbean - Paes de Barros, Ricardo; Ferreira, Francisco H.G.; Molinas Vega, Jose R.; Saavedra Chanduvi, Jaime (Washington, DC: World Bank, 2012)
Over the past decade, faster growth and smarter social policy have reversed the trend in Latin America's poverty. Too slowly and insufficiently, but undeniably, the percentage of Latinos who are poor has at long last begun to fall. This has shifted the political and policy debates from poverty toward inequality, something to be expected in a region that exhibits the world's most regressive distribution of development outcomes such as income, land ownership, and educational achievement. This book is a breakthrough in the measurement of human opportunity. It builds sophisticated formulas to answer a rather simple question: how much influence do personal circumstances have on the access that children get to the basic services that are necessary for a productive life? Needless to say, producing a methodology to measure human opportunity, and applying it across countries in one region, is just a first step. On the one hand, technical discussions and scientific vetting will continue, and refinements will surely follow. On the other, applying the new tool to a single country will allow for adjustments that make the findings much more useful to its policy realities. And fascinating comparative lessons could be learned by measuring human opportunity in developed countries across, say, the states of the United States or the nations of Europe. But the main message this book delivers remains a powerful one: it is possible to make equity a central purpose, if not the very definition, of development. That is, perhaps, it's most important contribution.